Student's perspective of e-learning initiatives at University Utara Malaysia - Mutum, Dilip; Md Isa, Mohd Azwardi (2004)
In line with the top management's vision of a moving towards World-class status and producing graduates equipped with the right skills, University Utara Malaysia has implemented several strategies. One of the most important is the use of information communications technology (ICT) as an important tool in enhancing the dissemination and retrieval of knowledge or E-learning. This includes steps such as the setting up of Wifi services and the setting up of an E-learning system. This exploratory study seeks to assesses the challenges and limitations of the ICT and E-learning facilities in the university from the user's perspective, specifically that of the undergraduate students. A questionnaire composed of closed as well as open-ended questions was used to elicit responses from 77 students taking the BIBM course in the Faculty of International Studies. This was with regard to their online activities as well as their opinion about the ICT facilities provided by the University. It was found that using e-mail and researching for course projects were the most popular online activities. Most of the students accessed the Internet in the University computer labs and it was found that they were not satisfied with the service, with most complaining about slow access speeds. However, most of them were satisfied with the LearningCare Learning Management System (LMS), which became operational in May 2002/2003 Semester. Most of the students were also not aware or didn't use the Wifi facilities provided by the University. The paper suggests some recommendations for improving the E-learning and ICT facilities of the University as well as areas for further research.